The philosophical journey : - Lawhead, William F. (McGraw Hill, 2011)
The Philosophical Journey: An Interactive Approach, is a text/reader which enhances comprehension of philosophical study by allowing the reader to ponder, explore and actively participate in the learning process. Philosophy becomes a personal journey to students through Bill Lawhead's innovative and unique pedagogy which delivers philosophical concepts through more digestible chunks.